1987
DOI: 10.1017/s0021859600080758
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary molybdenum and iron on copper status, puberty, fertility and oestrous cycles in cattle

Abstract: Two experiments were conducted to examine the effects of supplementation of a control diet of barley grain and barley straw containing 4 mg copper (Cu)/kg dry matter (D.M.) either with 5 mg molybdenum (Mo)/kg D.M. or with 500 or 800 mg iron (Fe)/kg D.M. on puberty, fertility and oestrous cycles of cattle. Puberty occurred normally in control, Fesupplemented and control animals on a restricted intake whereas it was delayed by 12 and 8 weeks respectively by Mo supplementation. This effect of Mo was not due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Therefore, a reduction in the production of androstenedione, as we have reported for TTM doses greater than 5, is likely to limit the production of oestradiol due to substrate limitation. The results of the present study are consistent with an effect of molybdenum-induced copper deficiency on the development of the preovulatory follicle, especially steroid secretion, and would therefore be expected to perturb both behavioural oestrus and ovulation to a varying degree, as has been observed in animals with molybdenum-induced copper responsive subfertility (Phillippo et al 1987, Du Plessis et al 1999a, 1999b. Further, it is well established that ovarian oestradiol plays a key role in controlling gamete transport and in priming the uterus for implantation, so that even if ovulation does occur, fertility rates are likely to be impaired if preovulatory oestradiol production is sub-optimal .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, a reduction in the production of androstenedione, as we have reported for TTM doses greater than 5, is likely to limit the production of oestradiol due to substrate limitation. The results of the present study are consistent with an effect of molybdenum-induced copper deficiency on the development of the preovulatory follicle, especially steroid secretion, and would therefore be expected to perturb both behavioural oestrus and ovulation to a varying degree, as has been observed in animals with molybdenum-induced copper responsive subfertility (Phillippo et al 1987, Du Plessis et al 1999a, 1999b. Further, it is well established that ovarian oestradiol plays a key role in controlling gamete transport and in priming the uterus for implantation, so that even if ovulation does occur, fertility rates are likely to be impaired if preovulatory oestradiol production is sub-optimal .…”
Section: Discussionsupporting
confidence: 89%
“…The effects of thiomolybdates in the whole animal have previously been shown to include reduced conception rates, anovulation and anoestrus, which were associated with a decreased release of LH (Phillippo et al 1987). The pre-ovulatory oestradiol peak is the endocrine signal responsible for induction of both behavioural oestrus and the preovulatory LH surge (Baird & McNeilly 1981) and the dominant follicle in ruminants is the source of over 96% of ovarian oestradiol secretion (Baird & Scaramuzzi 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diminished level of FSH and LH could be due to copper deficiency caused by molybdenum exposure (Phillippo et al, 1987). It was further elucidated by Haywood et al (2004) that reduced copper content make it unavailable for a copper-dependent enzyme peptidylglycine α-amidating mono-oxygenase (PAM) that appears to be crucial for the bioactivation of many peptide hormones, including FSH and LH.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a mineral acting as 1.66-2.22 g/dl in many areas of metabolism (Phillipo et al, 1987). However, Antunovic et al (2002) reported that although there was a marked increase in serum Fe levels depending on foetal growth particularly during the last trimester of pregnancy, while the levels decreased immediately before the lambing of Akkaraman ewes.…”
Section: Minerals Valuesmentioning
confidence: 99%